GAP Peptide Synthesis via Design of New GAP Protecting Group: An Fmoc/tBu Synthesis of Thymopentin Free from Polymers, Chromatography and Recrystallization - Seifert, Cole W. (European J Org Chem, 2016)
A novel method for Fmoc/tBu solution-phase peptide synthesis and the development of a new benzyl-type GAP protecting group is reported. This new GAP protecting group is utilized in place of a polymer support, facilitating C→N Fmoc peptide synthesis without chromatography, recrystallization, or polymer supports. The GAP group can be added and removed in high yield, and was used to synthesize over 1 gram of the immunostimulant, thymopentin, in high overall yield (83%) and purity (99%).